Nonoscillatory Solutions for Higher-Order Neutral Dynamic Equations on Time Scales - Taixiang Sun; Hongjian Xi; Xiaofeng Peng; Weiyong Yu (Abstract and Applied Analysis)
We study the higher-order neutral dynamic equation {a(t)[(x(t)−p(t)x(τ(t)))Δm]α}Δ+f(t,x(δ(t)))=0 for t∈[t0,∞)T and obtain some necessary and sufficient conditions for the existence of nonoscillatory bounded solutions for this equation.